Role of Crush Cytology for the Detection of Helicobacter Pylori in Gastroduodenal Diseases - Ahsan, K; Hossain, MZ; Uddin, MR (Journal of Dhaka Medical College, 2010)
Context: A cross-sectional study was carried out at the Department of Pathology, Dhaka Medical Collage, Dhaka and Immunology Laboratory, Laboratory Sciences Division of ICDDR,B, Dhaka during a period of 1 year from July, 2007 to June, 2008 to determine the efficacy of endoscopic crush cytology in the detection of Helicobacter pylori infection in gastroduodenal diseases. Clinically suspected cases of gastro-duodenal lesions and who had not taken antibiotics, omeprazole or bismuth salts for at least three weeks prior to endoscopy were selected. Patients who were clinically and endoscopically suspected of having malignancy were excluded from the study. A total of 110 such subjects were consecutively included in the study. The statistics used to analyze the data were descriptive statistics and components of accuracy test. Results: The sensitivity of crush cytology in correctly diagnosing H. pylori of those who had the disease was 89.3%, while the specificity of the test in correctly differentiating those who did not have H. pylori was 92.6% when compared against histopathological examination using Giemsa stain. However, a slightly low sensitivity (86.2%) without compromising with specificity (92.3%) was obtained when the crush cytology diagnosis was compared against histopathological examination using haematoxylin-eosin (H & E) stain. Conclusion: The study concludes that the diagnostic accuracy of crush smear cytology (sensitivity and specificity) for detection of Helicobacter pylori in gastric biopsy material is comparable to histopathology. Moreover, the technique is very simple, less expensive and less time consuming which gives clinicians added advantage in making a quicker decision. Key words: Cytology; Helicobacter pylori; Gastroduodenal disease. DOI: 10.3329/jdmc.v17i2.6589 J Dhaka Med Coll. 2008; 17(2) : 88-93